The Journal of Global Sport Management: An Introduction. Issue 1 (2nd April 2016) - Kim, Kihan
ABSTRACT: A new academic journal advancing the field of sport management is introduced. The Journal of Global Sport Management ( JGSM ) intends to serve as an interdisciplinary global platform for sport management research, involving academics from a wide range of disciplines both within and outside the conventional boundaries of sport management research. In JSGM 's inaugural issue, the first contributors will be introduced, the articles summarised and the structure of the editorial team presented.